Effect of sex and final fattening on ultrasound and carcass traits in Iberian pigs. - Ayuso, D; González, a; Hernández, F; Peña, F; Izquierdo, M (Meat science, 2014)
A hundred and twenty-five castrated Iberian pigs (61 males and 64 females, from 106.9 kg of live weight at star to 160.3 kg at slaughter) was used to investigate the effect of feeding system on carcass attributes (backfat thickness and loin area measured with ultrasound before slaughter, and intramuscular fat and weights and yields of hams, forelegs and loins after slaughter). Pigs were fattened outdoor under extensive conditions. There were 4 treatments: "montanera", M; "recebo", R; "cebo a campo", C; and high oleic fed, O). Ultrasound images were collected at two rib locations (10th and 14th). M and O groups had the highest fat thickness and loin area was lower in M than in C group. M and O showed higher carcass weight and yield than the other groups. The largest ham weight was for C and the lowest for M groups. Loin weight and yield were higher in M and R than the other two groups (O and C).
Keywords: Adipose Tissue; Adipose Tissue: chemistry; Adipose Tissue: ultrasonography; Animal Feed; Animal Feed: analysis; Animals; Body Weight; fatty acids; Fatty Acids: analysis; Female; Image Processing, Computer-Assisted; Male; meat; Meat: analysis; Muscle, Skeletal; Muscle, Skeletal: chemistry; Muscle, Skeletal: ultrasonography; Phenotype; Sex Factors; Swine